Top-Down and Bottom-Up Control in the Galápagos Upwelling System - Brandt, Margarita; Silva-Romero, Isabel; Fernández-Garnica, David; Agudo-Adriani, Esteban; Bove, Colleen B.; Bruno, John F. (Frontiers in Marine Science, 2022)
Increased standing biomass of macroalgal in upwelling zones is generally assumed to be the result of higher nutrient flux due to upwelled waters. However, other factors can strongly impact macroalgal communities. For example, herbivory and temperature, via their effects on primary producers and the metabolic demands of consumers, can also influence macroalgal biomass and productivity, respectively. We assessed the effects of nutrient availability, temperature, and herbivory on macroalgal biomass on a subtidal nearshore rocky reef in the Galápagos Islands. We manipulated nutrient availability and herbivory in field experiments performed in two seasons: the first during a cool, upwelling season, and the second during a warm, non-upwelling season. Excluding macro-herbivores had a clear effect on standing macroalgal biomass, independent of season or nutrient availability. However, we found different interactive effects of nutrients and macro-herbivores between the two seasons. During the cool season, macroalgal biomass was significantly higher in herbivore exclusions than in open areas under ambient nutrient conditions. However, when nutrients were added, macroalgal biomass was not significantly different across all herbivore treatments, which suggests reduced top-down control of herbivores (hence a greater standing algal biomass) in open areas. In the warm season, macroalgal biomass was significantly higher in herbivore exclusions compared to open treatments, both with and without nutrient addition. Furthermore, biomass reached 2X in herbivore exclusions with nutrient additions. Overall, our results support the hypothesis that macro-herbivores reduce macroalgal biomass in this system and suggest that nutrient availability, but not temperature, modulate herbivory. Spanish Abstract available in Supplementary Material.